2004
DOI: 10.1063/1.1814813
|View full text |Cite
|
Sign up to set email alerts
|

O 18 tracer diffusion in Pb(Zr,Ti)O3 thin films: A probe of local oxygen vacancy concentration

Abstract: A series of O18 tracer in-diffusion experiments have been conducted on state-of-the-art metal organic chemical vapor deposition–grown Pb(Zr,Ti)O3 (PZT) films. Prior to O18 incorporation, samples were preequilibrated in O216 at the same temperature and total pressure used for the following O218 isotope exchange anneal. The final O18 depth profiles were obtained using secondary ion mass spectroscopy (SIMS), which provides a depth resolution of 3–5Å. The SIMS results indicate that the O18 tracer diffusivity varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 29 publications
4
37
0
Order By: Relevance
“…While under ambient conditions such moderate heating does not change either the crystalline quality or the macroscopic domain structure of PZT, 27 in UHV it should partially remove atmospheric adsorbates from the sample surface, 28 as well as favor the redistribution of oxygen vacancies. 29 Indeed, during the annealing, we observe a global reversal of the as-grown up-oriented polarization, consistent with significant changes in the electrostatic boundary conditions at the surface. 30 In some samples, the heat treatment led to surface deterioration and the formation of particulates, although in most cases high surface quality was maintained.…”
Section: )O 3 Thin Filmsmentioning
confidence: 52%
See 1 more Smart Citation
“…While under ambient conditions such moderate heating does not change either the crystalline quality or the macroscopic domain structure of PZT, 27 in UHV it should partially remove atmospheric adsorbates from the sample surface, 28 as well as favor the redistribution of oxygen vacancies. 29 Indeed, during the annealing, we observe a global reversal of the as-grown up-oriented polarization, consistent with significant changes in the electrostatic boundary conditions at the surface. 30 In some samples, the heat treatment led to surface deterioration and the formation of particulates, although in most cases high surface quality was maintained.…”
Section: )O 3 Thin Filmsmentioning
confidence: 52%
“…30,33,34 Moreover, even at low-to-moderate temperatures extremely oxygen-rich or oxygen-poor environments can lead to the formation of a surface "skin layer" with very different vacancy densities from the bulk. 29 Finally, oxygen vacancy mobility depends very strongly on temperature, with residence times varying from 10 000 s at 0 C down to 0.0001 s at 150 C. 35 We therefore posit that during the annealing process, the changes in the depolarizing field resulting from the partial removal of surface adsorbates and the accompanying polarization reversal are compensated by the rapid redistribution of oxygen vacancies, as schematically illustrated in Fig. 4(c).…”
Section: )O 3 Thin Filmsmentioning
confidence: 99%
“…The defect charges are mainly oxygen vacancies, and lead vacancies are usually compensated for by adding excess lead when the PZT film is prepared. 26 Furthermore, we found that a small part of the defect charges in the film can be expelled by poling, and a large part of them is excited by UV lighting, which is verified by the evolution of polarization loops of PZT films by poling and UV lighting. We proposed that these excited defect charges can be pulled back into the film after the poling voltage was removed, so the time-dependent V c offset and photocurrent were studied.…”
Section: Introductionmentioning
confidence: 84%
“…In particular, it is ideally suited to probing the equilibrium spacecharge layer at the surface of a crystalline oxide. 54,58,59 Taking acceptor-doped SrTiO 3 as our example, we begin by describing why the combination of isotope exchange and SIMS analysis is capable of making space-charge layers "visible." 54 The technique is based on three points: (1) oxygen diffusion in SrTiO 3 takes place by a vacancy mechanism and is thus dependent on the concentration of oxygen vacancies; (2) in an equilibrium spacecharge layer depleted of oxygen vacancies, the local oxygen diffusion coefficient (proportional to the concentration of vacancies) is reduced in a manner that reflects the spatial variation of the electrical potential, because the vacancies are (doubly) charged ( Figure 10a); (3) when an isotope exchange experiment is carried out, the labeled isotope has to diffuse through this region of locally reduced diffusivity before entering the homogeneous bulk phase, and this gives rise to an additional isotope profile within the spacecharge layer (Figure 10b).…”
Section: Making Space-charge Layers "Visible"mentioning
confidence: 99%